(untitled) - Majercak, Jozef; Majercak, Peter (Doprava a spoje, 2006)
In the conditions of railways is more and more applied measurement of quality of provided services during transport chain in railway transport. Railway Company of Slovak republic is conscious of the need to analyze deficiencies during the transportation and to try to find solutions, which attract passengers on railways. This paper deals about this possibility